Macroeconomic Challenges of Scaling Up Aid to Africa : A Checklist for Practitioners - Yang, Yongzheng (International Monetary Fund, 2006)
Over the next decade, African countries are expected to be the largest beneficiaries of increased donor aid, which is intended to improve their prospects for achieving the Millennium Development Goals. This handbook will help these countries assess the macroeconomic implications of increased aid and respond to the associated policy challenges. The handbook is directed at policymakers, practicing economists in African countries, and the staffs of international financial institutions and donor agencies who participate in preparing medium-term strategies for African countries, including in the context of poverty reduction strategy papers. It provides five main guidelines for developing scaling-up scenarios to help countries identify important policy issues involved in using higher aid flows effectively: to absorb as much aid as possible, to boost growth in the short to medium term, to promote good governance and reduce corruption, to prepare an exit strategy should aid levels decrease, and to regularly reassess the policy mix.